Adenosine receptors in GtoPdb v.2021.2 - Fredholm, Bertil B.; Frenguelli, Bruno G.; Hills, Rebecca; IJzerman, Adriaan P.; Jacobson, Kenneth A.; Klotz, Karl-Norbert; Linden, Joel; Müller, Christa E.; Schwabe, Ulrich; Stiles, Gary L. (IUPHAR/BPS Guide to Pharmacology CITE, 2021)
Adenosine receptors (nomenclature as agreed by the NC-IUPHAR Subcommittee on Adenosine Receptors [110]) are activated by the endogenous ligand adenosine (potentially inosine also at A3 receptors). Crystal structures for the antagonist-bound [153, 313, 221, 61], agonist-bound [375, 203, 204] and G protein-bound A2A adenosine receptors [49] have been described. The structures of an antagonist-bound A1 receptor [128] and an adenosine-bound A1 receptor-Gi complex [86] have been resolved by cryo-electronmicroscopy. Another structure of an antagonist-bound A1 receptor obtained with X-ray crystallography has also been reported [57]. caffeine is a nonselective antagonist for adenosine receptors, while istradefylline, a selective A2A receptor antagonist, is on the market for the treatment of Parkinson's disease.